(untitled) (Numerus academy review, 2026)
Financial management is one of the most important areas of great interest, considering that the financial component occupies a prominent place in public policies, as it is the tool by which these policies are implemented, finances all facilities, projects are completed and the elected councils translate their political programmes into reality. The territorial community considers the small palace belonging to the region of Al-fahsAnjra(Tangier Tetouan al-Hoceima) among the poor Estes within the region, the revenues of its financial resources are weak and do not contribute to the financing of the group’s budget, which has increased its dependence on the State. From this point of view, we will try to highlight the issue of the territorial management as a component of the development action of the territorial commune (ksar sghir) on the one hand, and on the other hand we will try to address the social composition of the elected councils, as an important factor in the management of local public affairs.